Acute Management of Sepsis beyond 24 Hours - Premachandra, Antoine; Heming, Nicholas (Seminars in Respiratory and Critical Care Medicine, 2024)
Sepsis manifests as a dysregulated immune response to an infection, leading to tissue damage, organ failure, and potentially death or long-term health issues. Sepsis remains a major health challenge globally, causing approximately 50 million cases and 11 million deaths annually. Early management of sepsis focuses on source control, antimicrobial treatment, and supporting vital organ function. Subsequent care includes metabolic, nutritional, and immune therapies to address the complex needs of septic patients. Metabolic management is based on obtaining moderate glucose targets. Nutritional support aims to mitigate hypercatabolism and muscle wasting, but aggressive early nutrition does not improve outcomes and could even be harmful. Immune modulation is crucial due to the dual nature of sepsis-induced immune responses. Corticosteroids have shown benefits in shock and organ dysfunction reversal and in mortality reduction with current guidelines recommending them in vasopressor therapy-dependent patients. In conclusion, sepsis management beyond the initial hours requires a multifaceted approach, focusing on metabolic, nutritional, and immune system support tailored to individual patient needs to enhance survival and recovery.
Keywords: septic shock; metabolism; immunology; personalized medicine; intensive care unit